A channel matrix rank reduction method using space - time coding in a MIMO system / Jahangir Dadkhah Chimeh - Chimeh, Jahangir Dadkhah (Faculty of Electrical Engineering, Universiti Teknologi MARA, Shah Alam, 2017)
Massive MIMO has an important role in 5G and IoT, however provides hardware problems in the system. To reduce these challenges we introduce a method for channel matrix rank reduction which reduces the computations volume in a m×n MIMO system using space - time coding in this paper. We used this method to 4×2 system to change its rank to 2×2, however it may be used to any desirable higher order m×n Massive MIMO systems.